Murzynek B. by Artur Daniel Liskowacki - MONIKA BUJAK (Autobiografia, 2021)
This article is a review of the book Murzynek B. Arthur Daniel Liskowacki wrote his novel in a very characteristic way. Short, jagged sentences huddle in one long text. It looks like a train of thoughts, discussions and descriptions of events. The reader must pick up, guess, analyze and read very carefully to not get lost in this fight between good and evil, between black and white.